The relationship between macroeconomic variables with the movement of FTSE Bursa Malaysia Shariah EMAS Index price / Fatin Fashareena Misrom - Misrom, Fatin Fashareena (Faculty of Business and Management, 2011)
This paper will provide evidence of relationship between macroeconomic variables with the price movement of FTSE Bursa Malaysia Shariah EMAS Index. The selected macroeconomic variables used in this study are interest rate, inflation rates and industrial production index. The development of shariah stock market in Malaysia is the main influence to indicate this study. Islamic stock market is one of the important indicators to the Malaysian economic during this century.